Effects of fat and sodium bicarbonate on growth performance and stomach morphology in finishing pigs - Sorrell, S.P.; Kim, I.H.; Hines, Robert H.; Kennedy, G.A.; Burnham, L.L.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs fed diets with soybean oil consumed less feed; grew more efficiently; and had greater last-rib backfat thickness, keratosis, and ulceration in their stomachs than pigs fed diets without soybean oil. Pigs fed diets with NaHC03 tended to eat more feed and had numerically greater ADG, but feed/gain and carcass measurements were not affected. NaHC03 decreased ulceration scores only for pigs fed diets without added fat.
Keywords: Swine; Finishing pigs; Fat; Sodium bicarbonate; Ulcers